Proteomic insights into dual-species biofilm formation of E. coli and E. faecalis on urinary catheters - Kidon Sung; Miseon Park; Ohgew Kweon; Angel Paredes; Alena Savenka; Saeed A Khan (Scientific Reports)
Abstract Infections associated with urinary catheters are often caused by biofilms composed of various bacterial species that form on the catheters’ surfaces. In this study, we investigated the intricate interplay between Escherichia coli and Enterococcus faecalis during biofilm formation on urinary catheter segments using a dual-species culture model. We analyzed biofilm formation and global proteomic profiles to understand how these bacteria interact and adapt within a shared environment. Our findings demonstrated dynamic population shifts within the biofilms, with E. coli initially thriving in the presence of E. faecalis, then declining during biofilm development. E. faecalis exhibited a rapid decrease in cell numbers after 48 h in both single- and dual-species biofilms. Interestingly, the composition of the dual-species biofilms was remarkably diverse, with some predominantly composed of E. coli or of E. faecalis; others showed a balanced ratio of both species. Notably, elongated E. faecalis cells were observed in dual-species biofilms, a novel finding in mixed-species biofilm cultures. Proteomic analysis revealed distinct adaptive strategies E. coli and E. faecalis employed within biofilms. E. coli exhibited a more proactive response, emphasizing motility, transcription, and protein synthesis for biofilm establishment; whereas E. faecalis displayed a more reserved strategy, potentially downregulating metabolic activity, transcription, and translation in response to cohabitation with E. coli. Both E. coli and E. faecalis displayed significant downregulation of virulence-associated proteins when coexisting in dual-species biofilms. By delving deeper into these dynamics, we can gain a more comprehensive understanding of challenging biofilm-associated infections, paving the way for novel strategies to combat them.